Assessing Foreign Language Learners in Online Learning: Methods, Challenges and Strategies - Leni Amelia Suek (Universitas Nusa Cendana, 2022)
This paper is aimed at analysing methods, challenges and strategies of online assessment for foreign language learners during the Covid-19 Pandemic at a higher educational setting. The online questionnaires were distributed to lecturers of English Department of Nusa Cendana University. It was revealed that the lecturers assessed students’ language skills by project, quiz, exam, written assignment, online discussion and presentation. The main challenge was ineffective nature of online assessment because it cannot measure students’ language skills comprehensively and was prone to academic dishonesty. Various technical issues such as time management, Internet connection and miscommunication were faced by the English lecturers as well. However, they also applied several strategies to overcome those challenges including changing scoring system, lowering the standard, giving students extra time to complete the assignment, using online testing tools to score and store the assignment, instructing the assignment via video conference such as Zoom to avoid miscommunication. It is expected that lecturers are able to use various kinds of methods to assess their students’ foreign language abilities and to be able to overcome every challenge they encounter by applying meaningful strategies.